Power output stabilizing feature in perovskite solar cells at operating condition: Selective contact-dependent charge recombination dynamics. (July 2019) - Kim, Hui-Seon; Seo, Ji-Youn; Akin, Seckin; Simon, Elfriede; Fleischer, Maximilian; Zakeeruddin, Shaik M.; Grӓtzel, Michael; Hagfeldt, Anders
Abstract: Stabilized power output at maximum power point (mpp) has been considered as one of the most reliable parameters as it provides a key performance indicator for perovskite solar cells (PSCs) revealing the operational stability of the photovoltaic device. Here, we show the effect of selective contact on the power output change under mpp tracking, which closely correlates with the charge recombination dynamics with a time scale of minutes. The normal n-i-p cell architecture comprising cp-TiO2 /mp-TiO2 /perovskite/ spiro -MeOTAD (doped by either Li-TFSI or Zn-TFSI2 ) and the inverted p-i-n structure, NiOx /perovskite/PCBM, are examined to investigate the specific effect of the nature of the interface on operational stability. The normal structure with Li-TFSI shows a gradual performance decrease at mpp owing to the enhanced recombination at the interface between the perovskite and the spiro -MeOTAD, becoming the dominant recombination process, although the bulk-related recombination is suppressed. On the other hand, the inverted structure demonstrates an improved photocurrent at mpp due to the effectively suppressed recombination both in bulk and at the interface. Remarkably, the deteriorating performance of the normal structure with Li-TFSI at mpp is successfully avoided by replacing Li-TFSI with Zn-TFSI2, leading even to an increased power output with stable performance at mpp. Graphical abstract: Image 1 Highlights: The normal structure with Li-TFSI as a dopant for spiro-MeOTAD shows a pronounced recombination at the interface at mpp. This is responsible for a gradual performance decrease although the bulk-related recombination is suppressed. The unstable performance of the normal structure is resolved by replacing Li-TFSI with Zn-TFSI2 . The inverted structure shows a stable power output owing to the suppressed recombination both in bulk and at the interface.